"A great conspiracy": Self-directed learning among Protestant clergy in Russia - Wayne R. Kenney (Adult Education Research Conference, 1996)
This study investigated how Protestant clergy in Russia sought ministry education in the years prior to 1987 and what their education and ministry meant to them. Because formally schools and organized programs were forbidden, these clergy undertook clandestine, self-directed learning activities what on participant described as a great conspiracy. Their collective story presents new insights regarding assumptions, definitions and issues regarding self-directed learning, adult learners, and cultural and social contexts.